Cytology of Primary Salivary Gland-Type Tumors of the Lower Respiratory Tract: Report of 15 Cases and Review of the Literature - Saglietti, Chiara; Volante, Marco; La Rosa, Stefano; Letovanec, Igor; Pusztaszeri, Marc; Gatti, Gaia; Bongiovanni, Massimo (Frontiers in Medicine, 2017)
Primary pulmonary salivary gland-type tumors are rare neoplasms arising from the seromucinous submucosal glands of the lower respiratory tract, the most common of which are mucoepidermoid carcinoma and adenoid cystic carcinoma. They are morphologically indistinguishable from their salivary gland counterpart and recognizing them is a challenge, especially on cytological specimens. We analyzed 15 cases of histologically-proven primary salivary gland tumors of the lower respiratory tract to identify cytomorphological features and define potential diagnostic clues that might assist cytopathologists in the pre-operative diagnosis of these neoplasias. Three out of the four cases of adenoid cystic carcinomas showed the characteristic tridimensional cell clusters and hyaline globules, whereas the last one did not show malignant cells; only two cases of mucoepidermoid carcinoma presented the three characteristic cell types (i.e., squamous, intermediate and mucin-secreting) on cytology. Since these neoplasms are rare and do not have a completely specific set of cytological features, it is important for practicing cytopathologists to be aware of the possibility of encountering them, in specimens from patients with lower respiratory tract masses, in order to render the correct diagnosis.